Causes and Intervention Strategies to Reduce Childhood Obesity in Ambato - Carlos David Castañeda Guillot; Diego Fernando Vaca Sánchez; María Augusta Reyes Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
Foundation: childhood obesity constitutes a Public Health problem of widespread concern today. Objective: evaluate the implementation of an action program aimed at reducing the rate of childhood obesity in the population under study. Methods: a quasi-experimental study, before-after type without a control group, was carried out in children between 7 and 15 years old residing in Ambato, Ecuador, during the year 2022; The sample consisted of 350 children. The study was carried out in three phases; the first: for the diagnosis of knowledge patterns and gaps; the second: for the design and validation of the intervention program; and the third: to evaluate its effectiveness. Results: obese patients predominated in an age range of 13 years or more and were female. 86 % of patients showed excessive consumption of sweets and snacks, spending more than 30 hours a week in front of digital devices, and 73.1 % showed inappropriate family behaviors. An educational program was proposed with 5 sessions that includes: objectives, content and specific evaluations. The post-evaluation found a significant variation (p < 0.01) in the number of obese children, regular consumption of fruits and vegetables, and time spent in front of digital media. Conclusions: an educational intervention strategy was designed, aimed at promoting healthy lifestyles, both in children and in their parents and institutions. The intervention was effective in modifying the number of obese children, the regular consumption of fruits and vegetables, and the time spent in front of digital media.